Effects of Acute Tryptophan Depletion on Repetitive Behavior in Laying Hens - Birkl, Patrick; Chow, Jacqueline; McBride, Peter; Kjaer, Joergen B.; Kunze, Wolfgang; Forsythe, Paul; Harlander-Matauschek, Alexandra (Frontiers in Veterinary Science, 2019)
Repetitive feather pecking (FP) at the feather cover of other birds is one of the most important welfare problems in domestic chickens. It is not only characterized by motor symptoms, but also by an innate vulnerability of the serotonergic system. Moreover, the serotonergic system influences motor and cognitive function. Acute tryptophan depletion (ATD) is a widely used method for studying serotonergic function in mammals and has been recently validated in birds. However, a tryptophan-deficient amino acid mixture has never been tested on groups of birds to impact FP, nor has it been given to potentially impact motor performance. Therefore, we hypothesized that ATD would increase FP in laying hens under group housing conditions and pecking in a 5-second delay reward task in an operant chamber. One hundred sixty White Leghorn laying hens consisting of two genetic lines divergently selected to perform high (HFP) or low (LFP) levels of FP, and an unselected control line (CON), were kept in 10 groups consisting of 4 HFP, 3 LFP, and 9 CON genotypes. In a counterbalanced order, half of the groups were first subjected to an ATD treatment, while the other half were first given a nutritionally balanced control (BC) treatment, and vice versa, after which their FP behavior was observed. The effect of ATD/BC on repetitive pecking, motor performance, and cognition was investigated in a 5-second delayed reward task in an operant chamber with 10 phenotypic feather peckers, 10 recipients of FP and 10 neutrals (who neither performed nor received feather pecks). The birds were chosen based on their FP-phenotype. ATD given to groups of birds induced gentle, FP in all genotypes. Following ATD, phenotypic feather peckers performed more poorly during the delayed reward task than the other phenotypes, as seen by their higher number of repetitive, non-rewarded key and non-key pecks in the operant chamber. In conclusion, ATD impacted the hens’ social behavior by increasing the number of repetitive gentle feather pecks at conspecifics. Furthermore, feather peckers were more likely to peck while waiting for a reward after ATD, suggesting a role for the serotonergic system on cognition in these birds.